Phentolamine mesylate: It's role as a reversal agent for unwarranted prolonged local analgesia - Harpreet Singh Grover; Anil Gupta; Neha Saksena; Neha Saini (Wolters Kluwer Medknow Publications, 2015)
Administration of local anesthesia is an integral procedure prior to dental treatments to minimize the associated pain. It is learned that its effect stays more than the time required for the dental procedure to be completed. This prolonged soft tissue anesthesia (STA) can be detrimental, inconvenient, and unnecessary. Phentolamine mesylate, a Food and Drug Administration-approved drug essentially serves the purpose of faster recovery from numbness at the site of local anesthesia. This article reviews the development of the drug phentolamine mesylate and its indication as a local anesthetic reversal agent. A literature search for phentolamine mesylate as a STA reversal agent was conducted in PubMed using the terms "dental local anesthesia reversal, phentolamine mesylate" up to March 2014. The search was limited to articles published in English. The search revealed 13 PubMed indexed articles stating the development and application of phentolamine mesylate. Phentolamine mesylate is an important step in the progress of developing patient care as well as an aid to the dental clinician.